Conversations in Cardiology. Issue 5 (6th January 2014) - Kern, Morton J.; Applegate, Robert J.; Bell, Malcolm; Brilakis, Emmanouil S.; Butman, Samuel M.; Bach, Richard G.; Kaul, Prashant; Klein, Lloyd W.; Krucoff, Mitchell W.; Moore, Joseph A.; Price, Matthew J.; Rao, Sunil V.; et al.
<x xml:space="preserve">Abstract</x> Bridging for antiplatelet therapy remains a subject of debate with data favoring GP blockers but at a risk of bleeding. This Conversation in Cardiology addresses a key and often asked question about use of alternatives to P2Y12 agents in patients requiring surgery within 6 months after drug eluting stent implantation. © 2013 Wiley Periodicals, Inc.